The response of periodontal ligament collagen fibres and the thickness of inserting periodontal ligament fibre bundles at cementum pressure sites of fixed orthodontic appliances - Noengki Prameswari (Dental Journal (Majalah Kedokteran Gigi), 2007)
Previous research has indicated that there were several reactions in cellular activity and periodontal ligament collagen fibre as a response after orthodontic force application. Cementum has function to give attachment to collagen fibres of the periodontal ligament, maintaining the integrity of the root, helping to maintain the tooth in its functional position in the mouth, and being involved in tooth repair and regeneration so in the orthodontic tooth movement can induce changes in the cementum. The aim of this research is to investigate that fixed orthodontic appliance can change the amount of periodontal ligament collagen fibre and the thickness of inserting periodontal ligament fibre bundles at pressure site of cementum. This experimental study was held in laboratory with post test only control group design. Twenty two (22) premolar sample from 11 patient were divided into 2 groups. K group as control group (without treatment) and P group as treatment group (with using fixed orthodontic appliance). The amount of periodontal ligament collagen fibre and thickness of inserting periodontal ligament fibre bundles was examined by light microscopy and measured by image tool program. In the summary, there are increasing amount of periodontal ligament collagen fibre and the thickness of inserting periodontal ligament fibre bundles at cementum pressure sites as a normal response to remodeling and regenerating to orthodontic appliance and have function for strengthen adhering tooth cementum to the periodontal ligament.